2010
DOI: 10.1039/b925219n
|View full text |Cite
|
Sign up to set email alerts
|

Development of minimal models of the elastic properties of flexible and stiff polymer networks with permanent and thermoreversible cross-links

Abstract: We review the elasticity of flexible and stiff polymer networks with permanent cross-links and synthesize these results into a unifying polymer chain network model. This framework is then used to address how the network elasticity becomes modified when the network cross-linking is thermoreversible in nature, changes in the stability of the network with deformation, and the effect of a variable rate of network deformation on the non-linear elastic response. Comparisons are made between this class of simplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 77 publications
2
59
0
Order By: Relevance
“…3 with G 0 * = 430 Pa, Δh = -140 000 J mol -1 , and Δs = -475 J mol -1 K -1 . As discussed by Lin, et al [20], this sigmoidal temperature dependence of G 0 has been observed in a variety of amorphous solid materials [22][23][24], including both glass and gel materials. Evidently, this relation is a phenomenological counterpart for material stiffness to the Vogel-FulcherTammann relation describing the temperature dependence of the viscosity and structural relaxation time found in both glass-forming and self-assembled gel materials (e.g., see Kumar and Douglas [25]).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…3 with G 0 * = 430 Pa, Δh = -140 000 J mol -1 , and Δs = -475 J mol -1 K -1 . As discussed by Lin, et al [20], this sigmoidal temperature dependence of G 0 has been observed in a variety of amorphous solid materials [22][23][24], including both glass and gel materials. Evidently, this relation is a phenomenological counterpart for material stiffness to the Vogel-FulcherTammann relation describing the temperature dependence of the viscosity and structural relaxation time found in both glass-forming and self-assembled gel materials (e.g., see Kumar and Douglas [25]).…”
Section: Discussionmentioning
confidence: 96%
“…As described by Lin, et al [20], an effective medium treatment of rigidity percolation theory motivates taking the shear modulus of a self-assembled system to be proportional to the fraction, Φ, of associating species in the self-assembled state: (2) where G 0 * is the limiting value of the shear modulus in the fully self-assembled state, i.e., normally this means low temperatures but some materials can assemble upon heating. The temperature dependence of self-assembly upon cooling can be approximated by a simplified twostate model for the order parameter for the extent of self-assembly, Φ [20,21]:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expression has been employed previously to describe the large strain behavior of elastic, self-assembled triblock copolymer gels deformed in uniaxial compression 1 and shear 14 and equivalent functions have been applied to describe the non-linear elasticity of biological systems 33 and recently stiff polymer networks. 34 The physically associating solution is assumed to deform affinely, so that the local extension ratios We assume that strain energy is stored in deformed 'network strands' or 'bonds', which in our case correspond to bridging midblocks that span different endblock aggregates. In a dynamic system like the triblock solutions used in our experiments, molecules are constantly transforming from these load-bearing 'bridging' configurations to non-load-bearing 'looping' configurations, where both endblocks reside in the same aggregate.…”
Section: Constitutive Modelmentioning
confidence: 99%
“…While the mechanical behavior of semiflexible polymer networks with compliant and rigid crosslinks has been studied in detail both experimentally and theoretically [5][6][7][8][9][10] , the interplay between active mechanisms of stress generation through motor activity and passive strain hardening properties of crosslinks has only been considered very recently 4,7 . In this regard, reconstituted actin networks can be particularly useful, since the density of crosslinks and motors can be varied in a desired manner to gain insights into the mechanisms of strain hardening and nonlinear elastic response.…”
mentioning
confidence: 99%